2019
DOI: 10.1111/gfs.12455
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community dynamics and their contributions to organic acid production during the early stage of the ensiling of Napier grass (Pennisetum purpureum)

Abstract: The study aimed to disclose the microbial community dynamics and their contributions to organic acid production during the ensiling of Napier grass. Napier grass was harvested at the vegetative growth phase and ensiled for 30 days. Three silos were opened after 1, 2, 3, 5, 7, 14, and 30 days of ensiling respectively. The intensive fermentation was observed during the initial stage of ensiling, indicated by lower pH (<4.0) on d 2 of ensiling. Lactic acid (LA) was the primary fermentation product, although aceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 23 publications
4
26
2
Order By: Relevance
“…At the phylum level, the dominant bacteria were Firmicutes and Proteobacteria , similar to those reported by Wang et al [ 50 ]. Firmicutes can secrete various cellulases, lipases, and proteases and is able to survive in an anaerobic and low pH environment [ 51 ]. In addition, almost all LABs belong to Firmicutes .…”
Section: Discussionmentioning
confidence: 99%
“…At the phylum level, the dominant bacteria were Firmicutes and Proteobacteria , similar to those reported by Wang et al [ 50 ]. Firmicutes can secrete various cellulases, lipases, and proteases and is able to survive in an anaerobic and low pH environment [ 51 ]. In addition, almost all LABs belong to Firmicutes .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether inoculation with L. plantarum would quickly dominate and molasses would promote establishment of dominant bacteria in a combination of ensiled AF and RS, due to complex microbial sources in mixed silage. Next‐generation sequencing could be used to document the microbial dynamics of ensiled forages and provide insights regarding regulation of fermentation 12 …”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al . (2019b) also observed that the relative abundance of Weissella in Napier grass silages decreased below 2% after ensiling. Cai et al .…”
Section: Discussionmentioning
confidence: 87%